2015
DOI: 10.1091/mbc.e14-11-1553
|View full text |Cite
|
Sign up to set email alerts
|

MgcRacGAP restricts active RhoA at the cytokinetic furrow and both RhoA and Rac1 at cell–cell junctions in epithelial cells

Abstract: MgcRacGAP's role in regulating the spatiotemporal dynamics of active RhoA and Rac1 in epithelial cells is investigated. MgcRacGAP's GAP activity down-regulates RhoA at the furrow and both RhoA and Rac1 at cell–cell junctions in dividing epithelial cells and is required for successful cytokinesis and cell–cell junction structure. MgcRacGAP's ability to regulate adherens junctions is dependent on GAP activity and signaling via the RhoA pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 60 publications
3
53
0
Order By: Relevance
“…Given the requirement for Fmn1 in apical emergence (Sedzinski et al, 2016), we probed the role of RhoA in this process. We first measured the dynamics of RhoA activity using the active RhoA biosensor (rGBD), which has been shown previously to be effective in Xenopus (for examples, see Benink and Bement, 2005;Breznau et al, 2015;Reyes et al, 2014). We expressed GFP-rGBD in the mucociliary epithelium and found that throughout the expansion phase of the MCC apical surface, the fluorescence intensity of normalized active RhoA increased (Fig.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%
“…Given the requirement for Fmn1 in apical emergence (Sedzinski et al, 2016), we probed the role of RhoA in this process. We first measured the dynamics of RhoA activity using the active RhoA biosensor (rGBD), which has been shown previously to be effective in Xenopus (for examples, see Benink and Bement, 2005;Breznau et al, 2015;Reyes et al, 2014). We expressed GFP-rGBD in the mucociliary epithelium and found that throughout the expansion phase of the MCC apical surface, the fluorescence intensity of normalized active RhoA increased (Fig.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%
“…Embryos were injected with MO+MgcWT or MO+MgcSxNN along with probes for F-actin (mChe-UtrCH) and DNA (mChe-H2B), and movies of dividing cells were analyzed for defects in F-actin accumulation at the equatorial cortex of dividing cells (Fig. 5B) Breznau et al, 2015;Miller and Bement, 2009). Analysis of F-actin intensity plots at an equatorial region adjacent to the cleavage furrow at 25% ingression did not reveal a change in the breadth of F-actin accumulation (Fig.…”
Section: Mutation Of the Mgcracgap Sxip Motif Disrupts Equatorial Accmentioning
confidence: 99%
“…Endogenous Mgc was knocked down with a previously characterized morpholino oligonucleotide (MO), which effectively depletes Mgc protein levels and causes strong cytokinesis defects that can be rescued by expression of WT Mgc (MgcWT) mRNA (Breznau et al, 2015;Miller and Bement, 2009). MO-resistant Mgc-3×GFP was expressed at near-endogenous levels and localized at the overlapping anti-parallel MTs of the central spindle ( Fig.…”
Section: Mgcracgap Localizes To Microtubule Plus Ends At the Equatorimentioning
confidence: 99%
See 2 more Smart Citations